Integration von neuen Mobilitätsformen in Verkehrserhebungen und Verkehrsmodellierung - Kagerbauer, Martin (Schriftenreihe / Institut für Verkehrswesen, Karlsruher Institut für Technologie, 2022)
New technologies and forms of mobility are gradually becoming part of today's transportation supply. These new forms of mobility include, for example, car- or bikesharing and ridepooling, as well as new technologies such as electric mobility or automation. To take these new forms of mobility into account in transport planning tools, it is advisable to adapt both surveys and models.